4A marketing mix impacts on organic food purchase intention - Turk, Bahar; Ercis, Aysel (Serbian Journal of Management, 2017)
Nutrition is one of the main factors leading to a sustainable and healthy life. Consumers generally make decisions related to their daily nutrition and food choice. Therefore, it is important to determine the main potential factors affecting the final decision. These variables, also known as the 4As (acceptability, affordability, accessibility and awareness), affect consumers’ decisions in all stages of the purchase decision process. The purchase intention takes place at the beginning of this process. The determination of the most influential variable on the purchase intentions is crucial and helpful for each shareholders that concentrates on attracting consumers’ decisions in the decision process. The aim of this study is to provide a better insight in green purchase intention and to find which 4A attribute is more effective on purchase intention of organic foods. For this purpose, the data were analyzed by Analytic Hierarchy Process (AHP). The data were collected from 10 experts of Aarhus University’s MAPP Centre. Results revealed that "awareness" is the most effective among 4A mixed elements, followed by “affordability”, “accessibility” and “acceptability”.